(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the Worlds, and prayers and peace be upon the Master of the Messengers and his pure family and his chosen companions, and after...One of the topics that caught the attention of grammarians and dealt with it, and dived into the sea of ​​its features, is the multiplicity of syntactic aspects of the Qur’anic texts, and poetic texts, which led to controversy over the problem of syntax between grammarians and interpreters in directing the text.